In the margins : on the pleasures of reading and writing - Ferrante, Elena (Europa Editions, 2022)
A delightful collection of essays exploring reading and writing. "In the Margins" contains Elena Ferrante's latest reflections on literature, and the works and authors that have influenced her throughout her career.